River Run off Prediction Based on Rainfull DataUsing Tank Model - Sutoyo M. Yanuar J. Purwanto (PERTETA, 1999)
River run ofl model using tank model has been formulated to the natural river of Cidanau, Serang, West Java. The model consists of four lanks represent four land use zones. The parameter of the tanks were optimized using the observed data of injiltration capacity, daily rainfall and daily river discharge for an entire years. The advantages of this model is determination of the Jirst tank parameter using injiltration capacity. This parameter was directlydetermined based on in3ltration measurement for the respective land use zone. The application of this model was utilized for revising the discharge data since several period of the recorded data were not accurate.